A dual-band unequal power divider with flexible choice of implementation. Issue 2 (20th January 2015) - Tang, Cong; Fan, Yong; Song, Kaijun
Abstract : In this paper, a new asymmetric structure is proposed for the dual-band unequal application, in which both open- and short-ended stubs are applied. Closed-form design equations are obtained for the proposed power divider using the modified even- and odd-mode analysis method. It is observed that the proposed power divider can operate at high frequency ratio from 2.3 to 3.7 and has a wide operating band. Besides, this proposed circuit can offer flexibility in fabrication. For verification, two power dividers operate at 1/2.5 GHz with different values of line impedance are fabricated and tested. There is good agreement between simulation and experimental results, validating the proposed design concepts.